Islamic Law Review of Judge Considerations in Agreeing to Marriage Dispensation (Case Study in The Klaten Religious Court) - Berlian Fajrul Falakh (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This study explains the review of Islamic law on the Judge's considerations in determining marriage dispensation at the Klaten Religious Court. This research is library research by writing and clarifying data from various written sources at the Klaten Religious Court. Moreover, it is supported by field research in the form of interviews with judges and data collection of primary legal information for the Judge's considerations in providing marriage dispensation for the underage bride and groom couples and normative, juridical reviews regarding the issue of judges' considerations in determining marriage dispensations. This research shows that the legal considerations of marriage dispensation by the judges of the Klaten Religious Court are Law Number 1 of 1974 Article 7, paragraphs (1) and (2) concerning marriage. Whereas normatively, it is the fiqhiyah rule of "maintaining benefit and rejecting harm" for all parties and society. The Judge's consideration in determining the dispensation of marriage has been in line with one of the fiqh rules, namely the Mashlahah Mursalah, which explains and stipulates the legal provisions. Penelitian ini bertujuan untuk menjelaskan dispensasi nikah yang ditetapkan oleh Hakim Pengadilan Agama Klaten pada pertimbangannya ditinjau dari Hukum Islam. Dengan sifat penelitian (library research) dari Pengadilan Agama Klaten berupa sumber tertulis, dengan cara mengklarifikasi data-datanya. Dan didukung (field research), dengan mewawancarai para hakim, dan mengumpulkan informasi pertimbangan-petimbangan Hakim pada penetapan dispensasi nikah terhadap pemohon dan tinjauan normative yuridis terkait pertimbangan pada penetapan dispensasi nikah. Dari penelitian ini, ditunjukkan bahwa pertimbangan-pertimbangan para Hakim Pengadilan Agama Klaten menurut yuridis ialah UU No1 1974 Pasal 7 ayat (1) dan (2) tentang Perkawinan. Sementara dari normative ialah kaidah fiqhiyah tentang “menjaga kemaslahatan dan menolak kemudharatan”. Dan pertimbangan terkait dispensasi nikah pada penetapannya telah searah dengan kaidah fiqh, yaitu Mashlahah Mursalah.